Linking theory and practice: the case of TESL trainee teachers / Siti Salina Ghazali and Lee Lai Fong - Ghazali, Siti Salina; Lee, Lai Fong (ACRULeT, Faculty of Education & UiTM Press, 2008)
The purpose of this study was to investigate TESL trainee teachers' insights on the link between theory and practice. This study also sought to find out how they viewed the effectiveness of the teacher preparation programme in terms of preparing them to teach secondary school students. The study involved 79 Teaching English as a Second Language (TESL) Part 7 and 8 trainee teachers from the Faculty of Education, UiTM selected through a purposive sampling procedure. This study adopted both quantitative and qualitative methods to ensure that a wide coverage of areas and detailed explanations of those areas could be gathered. To obtain the quantitative data, the survey method was employed and the instrument need was a questionnaire. On the other hand, to get the qualitative data, interviews were conducted and journal entries were scrutinised. The findings revealed that the trainees felt that they were well-prepared in three crucial areas which were field knowledge, pedagogical knowledge and professional knowledge. The results also indicated that gender and academic performance have no influence on the trainees' perceptions. At the end of the paper, implications of the study were discussed and recommendations were made to further strengthen the teacher education programme at the Faculty of Education in UiTM.